Mother tongue interference in English writing among Tamil school students - Prashana Nair Kumaran,; Pramela Krish, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Writing is considered one of the most challenging language skills that students need to acquire. In Malaysia’s vernacular schools, students encounter several challenges as they need to write in variety of languages: their mother tongue, Malay and English. The students’ mother tongue can interfere when writing in English due to the difference of structures between these languages. This paper aims to explore this issue further by examining how the Tamil language in particular influences its young native speakers’ writing of English essays. For the purpose of this study, 30 writing samples of Year 5 students from a Tamil school were studied in terms of structure, vocabulary usage, and spelling. Errors committed in the essays were identified, categorized and scrutinized. The findings reveal that the main issues in the students’ writings are related to grammar, direct translation of the Tamil language, vocabulary and spelling. While we need to understand why and how mother tongue interference affects their writing, it is crucial to curb these writing issues at the primary school level so that such errors can be minimized as they will be doing higher levels of writing. The findings of the study suggest that students need to recognise the differences between their first language (L1) and the English language and learn to understand the different features and structures of the languages in order to write communicative and correct sentences.